Prospective validation of an immunohistochemical panel (glypican 3, heat shock protein 70 and glutamine synthetase) in liver biopsies for diagnosis of very early hepatocellular carcinoma. Issue 10 (27th January 2012) - Tremosini, Silvia; Forner, Alejandro; Boix, Loreto; Vilana, Ramon; Bianchi, Luis; Reig, Maria; Rimola, Jordi; Rodríguez-Lope, Carlos; Ayuso, Carmen; Solé, Manel; Bruix, Jordi
Abstract : Background and aims: Conventional pathological analysis fails to achieve sufficient sensitivity and specificity for the diagnosis of hepatocellular carcinoma (HCC) in small nodules. Immunohistochemical staining for glypican 3 (GPC3), heat shock protein 70 (HSP70) and glutamine synthetase (GS) has been suggested to allow a confident diagnosis but no prospective study has established the diagnostic accuracy of this approach. The aim of this study is to assess prospectively the diagnostic accuracy of a panel of markers (GPC3, HSP70, GS) for the diagnosis of HCC in patients with cirrhosis with a small (5–20 mm) nodule detected by ultrasound screening. Methods: Sixty patients with cirrhosis with a single nodule 5–20 mm newly detected by ultrasound were included in the study. Contrast-enhanced ultrasound, magnetic resonance and fine needle biopsy of the nodule (gold standard) were performed; the biopsy was repeated in case of diagnostic failures. Three consecutive sections of the first biopsy sample with meaningful material were stained with antibodies against GPC3, HSP70 and GS. Results: Forty patients were diagnosed with HCC. The sensitivity and specificity for HCC diagnosis were: GPC3 57.5% and 95%, HSP70 57.5% and 85%, GS 50% and 90%, respectively. The sensitivity and specificity of the different combinations were: GPC3+HSP70 40% and 100%; GPC3+GS 35% and 100%; HSP70+GS 35% and 100%; GPC3+HSP70+GS 25% and 100%. When at least two of the markers were positive (regardless of which), the sensitivity and specificity were 60% and 100%, respectively. Conventional pathological analysis yielded three false negative results, but the addition of this panel only correctly classified one of these cases as HCC. Conclusion: These data within a prospective study establish the clinical usefulness of this panel of markers for the diagnosis of early HCC. However, the panel only slightly increases the diagnostic accuracy in an expert setting.